Pengaruh Nilai Investasi, Tingkat Upah, Dan Nilai Produksi Terhadap Penyerapan Tenaga Kerja Studi Kasus Pada Konveksi Di Desa Kota Gajah Timur Kecamatan Kota Gajah Lampung Tengah - Rahayu, Sri Retnaning; Suryadi, Suryadi; Alvian, Rio Sandi (Universitas Muhammadiyah Metro, 2023)
This research aims to determine the effect of investment value, wage level, and productionvalue on labor absorption in convection in the village of East Gajah City, Central LampungCity Gajah District. By distributing questionnaires in the form of questions regardinginvestment value, wage levels, and production value on energy absorption, then processingthem using SPSS 20 with a classic assumption testing approach using normality, linearity,and homogeneity methods. This research uses quantitative methods with multiple linearregression analysis, partial test, F test, determination to determine the effect of investmentvalue, wage level, and production value on labor absorption in convection in the village ofKota Gajah Timur, Kota Gajah district, Central Lampung. The partial research results showthat simultaneously the investment value, wage level and production value have a positiveand significant effect on labor absorption.